Collaborative market development as a propoor and pro-environmental strategy - Anne Marie Tremblay (2018)
Litchi growers of the Hmong ethnic minority in hillsides of northern Thailand have received consistently low prices for their fresh litchi fruits in past years. Concerns over sustainable livelihoods and land use have prompted a group of academics from University of Hohenheim, Germany, and two institutes from Chiang Mai University, Thailand, to collaborate and invite farmers to initiate talks with a large supermarket chain that aims to buy directly from growers, thus bypassing middlemen and guaranteeing higher prices. The prospect of higher financial benefits has incited a group of farmers from several villages to comply with Good Agricultural Practices (GAP) guidelines, reduce the use of hazardous agrochemicals, form a cooperative and adapt cultivation methods. Drawing on qualitative research methods and an action-research approach, this pilot case study provides key insights into how collaboration between academics, smallholder farmers and large business actors can be fostered towards market relationships that are economically, socially and environmentally sustainable. © Practical Action Publishing 2209.